Construction of Data Acquisition and Processing System for Diagnostics Based on TSN Fiber Network at ASIPP NBI System. (4th July 2022) - Yu, Ling; Xu, Yongjian; Peng, Xufeng; Liu, Wei; Xie, Yahong
Abstract: According to the development trend of the international neutral beam injector diagnostic technology, it is planned to design a multichannel Langmuir electrostatic probe diagnostic system for the Comprehensive Research Facility for Fusion Technology negative-ion-based beam injector prototype. The probes are installed at different components of the neutral beam device to obtain plasma parameters. As the probes are at different positions and different potentials, conventional data acquisition systems, which are based on the traditional Ethernet protocol in publicly available resources, cannot meet the requirements of potential isolation and synchronous acquisition with high time resolution in the experiment. A data acquisition and processing system that is based on the fiber optic network of the Time Sensitive Networking protocol is put forward that solves the synchronous acquisition of signals at different potentials with high time resolution to achieve data processing. It provides the technical means for the study of plasma characteristics of the radio frequency negative ion source.